Animated exploring of huge software systems - Wang, Liqun (University of Ottawa (Canada), 2003)
There are many software visualization tools available today to help software engineers to explore software systems. However, when a system is huge, some of these tools do not satisfy the exploration requirements. The big problem is that the techniques the tools use do not provide an effective display and access mechanism to handle huge information spaces within the limitations imposed by available screen space. To alleviate the problem, this thesis describes methods that help users to explore huge software systems. In particular, we apply dynamic browsing incorporating such details as an extra result box mechanism, plus pattern based searching to help users to handle large query results. Then the thesis introduces the algorithms we apply to generate the layouts. We propose the radial angle model to visualize the internal structures of rooted trees. Also we apply the spring model to visualize the external structures among rooted trees. Next, the thesis describes various animation methods we use to smooth the transitions, track the focus of exploration, clarify unexpected results, and illustrate complex operations. In addition, we modify traditional camera animation, and propose an animation timing scheme 'slow-in fast-out' to exaggerate the reality. Next, the thesis describes a series of experiments we conducted to assess the effectiveness of the browsing, layout algorithm and animation techniques we implemented. Finally the thesis describes how we use the analysis of the experiment results to guide our future research.
Keywords: Engineering, System Science.; Computer Science.